Growth of tree species and sugarcane production in agroforestry systems - CARON,BRAULIO O. (2018)
Abstract The appropriate choice of tree species and planting arrangement for use in agroforestry systems is very important in order to maximize productivity and sustainability. The aim of this study was to evaluate the growth of five tree species and its effect on sugarcane yields in different planting arrays in agroforestry systems. The study was conducted from 2007 to 2011 in the city of Frederico Westphalen, RS, Brazil. The five studied tree species were: guapuruvu (Schizolobium parahybae), bracatinga (Mimosa scabrella), canafístula (Peltophorum dubium), angico-vermelho (Parapiptadenia rigida) and eucalypt (Eucalyptus urophylla S.T. Blake x Eucalyptus grandis Hill ex Maiden). Root collar diameter, diameter at breast height, plant height and mean diameter of crown were evaluated for four years with an interval of 90 days between assessments. Yield data for sugarcane were collected in June 2009, 2010, and 2011. Eucalypt presented the greatest root collar diameter values, diameter at breast height, crown development, and plant height. Angico-vermelho, canafístula and eucalypt presented a higher growth in the strip system, while guapuruvu presented the greater growth in the line system. Bracatinga was not influenced by an arrangement in the agroforestry systems. Sugarcane presented greater production in the understory of angico and bracatinga.